Student Work in VCC Libraries: From Mannequins in the Library to a Car on the Third Floor - Oldenburg, Kristina (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
A range of student creations decorates Vancouver Community College Libraries. These showcase products from trade and design programs. The downtown campus library features mannequins with clothing designed and created by students in addition to display cases of student-made jewelry. We also exhibit styled wigs from students’ trades skills competitions and framed illustrations from the digital graphic design and drafting programs. The Broadway library has a small study room that the college’s Automotive Collision and Refinishing (ACR) department created from a Smart Car. ACR students also paint our book trucks to practice different designs, techniques, and finishes. Displaying student projects makes the library space more visually interesting. Moreover, the ACR contributions are functional items for the library’s operation. Displaying student projects also facilitates library outreach with shop- and studio-based programs. Furthermore, the work aligns with VCC’s provision of experiential learning. This project report outlines a successful partnership for library outreach with instructional departments. It includes lessons learned about internal and external communication in project management and what we attribute our successes to for our related event planning.